The rewritten equation for the given equation is [tex]x=\frac{h+g}{-f}[/tex]. So, option C is correct.
A linear equation given in the form ax + b = c can be rewritten to solve for x as below:
ax + b = c
⇒ ax = c - b
∴ x = (c - b)/a
So, here the basic operations such as addition, subtraction, multiplication, and division are used on both sides to rewrite the given equation for solving x.
Given equation is -fx - g = h
Step 1: Adding 'g' on both sides
-fx - g + g = h + g
⇒ -fx = h + g
Step 2: Dividing by '-f' on both sides
-fx = h + g
⇒ -fx/-f = (h + g)/-f
∴ x = (h + g)/-f
Therefore, the rewritten equation to solve for x is x = (h + g)/-f.
Learn more about solving an equation here:
https://brainly.com/question/25678139
#SPJ4
Disclaimer: The given question was incomplete in the portal. Here is the complete question.
Question: Select the correct answer. which equation is correctly rewritten to solve for x?
Equation: -fx = h + g
A. x = (g - h)/f
B. x = (h - g)/-f
C. x = (h + g)/-f
D. x = (h + g)/f